L-cysteine, glycine and dl-threonine in the treatment of hypostatic leg ulceration a placebo-controlled study - Harvey, S G (Interim guidelines for the control of infections with Vero cytotoxin producing Escherichia coli (VTEC). Subcommittee of the PHLS Working Group on Vero cytotoxin producing Escherichia coli (VTEC), 1985)
A randomized, double-blind, placebo-controlled trial was carried out in 22 patients with hypostatic leg ulceration. Patients were treated topically with either a cream containing the amino acids l-cysteine, glycine and dl-threonine or the cream base alone (placebo). Most patients had their leg ulcers treated and dressed 3-times per week for 12 weeks. Clinical assessments were conducted at weekly intervals and data from 21 of the 22 patients were available for statistical analysis. The results revealed that the degree of healing and decrease of pain were significantly better in the group of patients receiving the amino acid combination. It would appear from this study that l-cysteine, glycine and dl-threonine in combination are of value in promoting would healing in hypostatic leg ulceration